2016
DOI: 10.5001/omj.2016.36
|View full text |Cite
|
Sign up to set email alerts
|

Early Oral Feeding After Surgery for Upper Gastrointestinal Malignancies: A Prospective Cohort Study

Abstract: EOF is safe following esophageal and gastric cancer surgery and results in faster recovery and hospital discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Seven of the 15 studies were randomised control trials, [17][18][19][20][21][22][23] six studies were cohort studies [24][25][26][27][28][29] and two were non-randomised trials. 30,31 The study by Hur et al 31 was a pilot to a larger study; 19 however, both were included in this review because they included different participant cohorts. The 15 studies included a total of 2517 participants.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven of the 15 studies were randomised control trials, [17][18][19][20][21][22][23] six studies were cohort studies [24][25][26][27][28][29] and two were non-randomised trials. 30,31 The study by Hur et al 31 was a pilot to a larger study; 19 however, both were included in this review because they included different participant cohorts. The 15 studies included a total of 2517 participants.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…Comparator groups included historical cohorts in five studies 24,[26][27][28][29] receiving usual care as defined by the authors and concurrent controls in the remaining 10 studies. [17][18][19][20][21][22][23]25,30 Within the included studies, sample size ranged between 34 and 552 participants. Out of the 15 studies, 10 [17][18][19][20]23,[25][26][27]29,31 examined patients with gastric cancer, undergoing partial and/or total gastrectomy.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…Malnutrition actually worsens upon the inclusion of the different treatments (chemotherapy, radiotherapy and operation), further worsening the patient’s general condition. It is paramount that adequate nutritional needs be met before, during and after treatment 13 .…”
Section: Introductionmentioning
confidence: 99%
“…So far, there have been studies showing that patients who underwent gastrectomy can be supported by early postoperative enteral nutrition[ 3 - 5 ]. Moreover, Shoar et al[ 20 ] showed that for patients with upper gastrointestinal malignant tumors, EOF after surgery can lead to faster recovery and shorter postoperative hospitalization. Lopes et al[ 21 ] also indicated that early oral diet was safe and viable for patients undergoing upper gastrointestinal surgery.…”
Section: Discussionmentioning
confidence: 99%